Degradation of interfacial adhesion strength within photovoltaic mini‐modules during damp‐heat exposure. (3rd February 2014) - Wu, Dan; Zhu, Jiang; Betts, Thomas R.; Gottschalg, Ralph
ABSTRACT The degradation of adhesion strength between the back sheet and encapsulant due to moisture penetration has been investigated for commercial crystalline silicon photovoltaic mini‐modules. The damp‐heat tests originating from the International Electrotechnical Commission qualification test were carried out at five different temperature and relative humidity (RH) conditions (95 °C/85% RH, 85 °C/85% RH, 65 °C/85% RH, 85 °C/65% RH and 85 °C/45% RH). The adhesion strength was measured by 90° peel tests, carried out at specified time intervals during degradation. Several visible defects were observed, including delamination, moisture ingress and bubble formation. The adhesion strength showed a stretched exponential decay with time, and significant influence of test conditions was demonstrated. A humidity dose model was proposed by assuming micro‐climates seen by the modules, that is, surface relative humidity of the back sheet as the driving factor for an Arrhenius‐based model using temperature as accelerating factor. The correlation between adhesion strength degradation and humidity dose was investigated through linear and exponential models. Results showed that the conventional linear model failed to represent the relationship while the exponential model fitted to this correlation with extracted activation energy (Ea) of around 63 kJ/mol. This provides a model for the estimation of adhesion strength decay in dependence of the humidity conditions. © 2014 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons, Ltd.